The global financial burden of humanitarian disasters: Leveraging GDP variation in the age of climate change. (March 2021) - McDougal, Topher L.; Patterson, John H.
Abstract: We quantify the global spending burden of humanitarian disaster response. While international response flows are well documented, global domestic spending on disasters is virtually unknown in any comprehensive way. We employ log-log fixed-effects models to estimate international humanitarian disaster response spending as recorded by UNOCHA's Financial Tracking Service (FTS) by recipient country and year, as a function of GDP per capita. Conservatively assuming all humanitarian disaster response spending in the poorest countries originates from without, we calculate a Population Attributable Fraction for the proportion of total spending attributable to GDP per capita, reverse-calculating yearly estimates of total humanitarian disaster response spending. We find global humanitarian expenditures to be roughly 13 times as high as official FTS figures, or around $367 billion annually. Finally, we use Simultaneous Equation Models to examine how total humanitarian disaster response spending is influenced by climate change (proxied by NASA's GISS Surface Temperature data). We find each 1° C rise in 5-year temperature anomalies would require an annual 3.1% (95% CI: 0.18%–6.01%) rise in humanitarian spending. In total, we estimate a further 1° C rise in global temperatures would require total annual humanitarian expenditures of approximately $1 trillion, or about 0.75% of worldwide 2019 GDP, in order to maintain current levels of humanitarian needs coverage. We find climate change to influence humanitarian spending only via GDP per capita and disaster hazard exposure, even though temperature anomalies predict significant increases to disaster vulnerability. Highlights: Total humanitarian spending is 13 times as high as official figures: $367 billion. 1 °C global temperature rise implies disaster spending of $1 trillion, 0.75% of GDP. GDP per capita is the most reliably significant predictor of international flows. Temperature anomalies predict significant increases to disaster vulnerability.